The Bachelor of Library Science graduates of the Institute of Library Science, University of the Philippines, AY 1964-1993 an employment profile - Serrano, Florida V. 1959-
One significant observation of the study is the favorable marketability of the BLS graduates. To ensure that the high regard and positive demand for the graduates will continue, it is recommended that the ILS's methods of teaching and techniques be enhanced and more modern facilities and equipment be introduced. In line with this, a periodic evaluation of the BLS program should be done by the school officials to make it more attuned to recent trends in information technology and in order to keep pace with the demands of the changing world.